P2X7 purinergic receptor plays a critical role in maintaining T-cell homeostasis and preventing lupus pathogenesis - Mellouk, Amine; Hutteau-Hamel, Tom; Legrand, Julie; Safya, Hanaa; Benbijja, Mohcine; Mercier-Nomé, Françoise; Benihoud, Karim; Kanellopoulos, Jean M.; Bobé, Pierre (Frontiers in Immunology, 2022)
The severe lymphoproliferative and lupus diseases developed by MRL/lpr mice depend on interactions between the Faslpr mutation and MRL genetic background. Thus, the Faslpr mutation causes limited disease in C57BL/6 mice. We previously found that accumulating B220+ CD4–CD8– double negative (DN) T cells in MRL/lpr mice show defective P2X7 receptor (P2X7)-induced cellular functions, suggesting that P2X7 contributes to T-cell homeostasis, along with Fas. Therefore, we generated a B6/lpr mouse strain (called B6/lpr-P2X7KO) carrying homozygous P2X7 knockout alleles. B6/lpr-P2X7KO mice accumulated high numbers of FasL-expressing B220+ DN T cells of CD45RBhighCD44high effector/memory CD8+ T-cell origin and developed severe lupus, characterized by leukocyte infiltration into the tissues, high levels of IgG anti-dsDNA and rheumatoid factor autoantibodies, and marked cytokine network dysregulation. B6/lpr-P2X7KO mice also exhibited a considerably reduced lifespan. P2X7 is therefore a novel regulator of T-cell homeostasis, of which cooperation with Fas is critical to prevent lymphoaccumulation and autoimmunity.